Development of an Experiential Learning Model for Exploring the Natural Surroundings (EJAS) by Utilizing Forests as a Learning Resource at the Leuser Nature School - Tarigan, Lola Zeramenda Br; Tambunan, Muhammad Iqbal Haitame; Sularno, Sularno (Pusdikra Publishing, 2025)
The research objectives are: (1) To produce a learning model product for exploring the surrounding natural environment using the forest as a learning resource for students at Leuser Nature School. (2) To find out the practicality level of the EJAS learning model by utilizing the Forest as a learning resource (3) The effectiveness of the E JAS model by utilizing the Forest as a learning resource on improving learning outcomes and environmentally conscious behavior. Research and development Borg and Gall is a study used in developing the EJAS learning model by utilizing the Forest as a learning resource for Leuser Nature School students. Expert validation of the EJAS learning model shows an average value of 91.7% with a very valid category. The results of the trials in all three stages are in the very practical category with an average value of 92.3%. Learning outcomes appear significant with an average learning completion score of 60.92 and an average N-Gain value of 0.609 (moderate to quite high category). Students' environmental behavior has an average of 4.15. So the EJAS model can be an alternative learning strategy that is not only effective in improving cognitive learning outcomes, but also in forming attitudes and character values of Leuser Nature School students.